2008
DOI: 10.2174/1874192400802010110
|View full text |Cite
|
Sign up to set email alerts
|

Statin Treatment, Carotid Atherosclerotic Plaque Macrophage Infiltration and Circulating Inflammatory Markers

Abstract: Abstract:Backround: Statin treatment is considered as first line therapy in patients with atherosclerotic disease. We evaluated the effect of pre-treatment with statins on carotid plaque infiltration by macrophages and on the circulating levels of proinflammatory cytokines in patients who underwent carotid endarterectomy. Patients and Methods:One hundred fourteen patients were enrolled; 89 men and 25 women (mean age 67±8 years; range 42-83 years). Fifty three patients (46%) were on statin treatment at least 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…12 Moreover, we have recently shown that patients on statins have similar macrophage accumulation in their carotid atherosclerotic plaques compared with patients not on statins. 32 The high macrophage infiltration in the Hp 2-2 group suggests a potential role of Hp genotype in the evolution of carotid plaque and plaque instability. Proposed pathogenetic mechanisms involve the impaired clearance of Hb-derived iron in Hp 2-2 plaques and the increased oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…12 Moreover, we have recently shown that patients on statins have similar macrophage accumulation in their carotid atherosclerotic plaques compared with patients not on statins. 32 The high macrophage infiltration in the Hp 2-2 group suggests a potential role of Hp genotype in the evolution of carotid plaque and plaque instability. Proposed pathogenetic mechanisms involve the impaired clearance of Hb-derived iron in Hp 2-2 plaques and the increased oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, also the study of Koutouzis and co-workers found a decrease of the hs-CRP level in patients treated with statins. However, the accumulation of macrophages in carotid plaques was not significantly lower in patients taking statins (51). Intensive lipid-lowering therapy, utilizing statin medication was more effective in the prevention of cardiovascular events in patients after a transient ischemic attack (TIA) and ischemic stroke than a moderate lowering of lipids.…”
Section: Evidence Of Inflammation Of Atherosclerotic Plaques and Therapeutic Interventionsmentioning
confidence: 96%
“…[65][66][67] Statin treatment is considered as first-line therapy in patients with atherosclerotic disease. Koutouzis et al 68 evaluated the effect of pretreatment with statins on carotid plaque infiltration by macrophages and on the circulating levels of proinflammatory cytokines in patients who underwent CEA. They concluded that patients on statins have similar macrophage accumulation in their carotid atherosclerotic plaques compared with patients not on statins.…”
Section: Statins and Hscrpmentioning
confidence: 99%
“…Inflammatory markers were also similar in both groups except for hsCRP which was significantly lower in those taking statins. 68 The ability of statin agents to lower hsCRP in a cholesterolindependent manner was first described in the analyses of data from the Cholesterol and Recurrent Events (CARE) trial, 69,70 a randomized evaluation of pravastatin in the secondary prevention of acute coronary events conducted among 4159 patients with a prior history of MI who had LDL-C levels between 115 and 175 mg/dL (2.98 and 4.53 mmol/L). They concluded that relative risk reduction associated with statin therapy was significantly greater in the presence of inflammation and elevated hsCRP than in its absence.…”
Section: Statins and Hscrpmentioning
confidence: 99%
See 1 more Smart Citation